A Non‐Conjugated Polymer Acceptor for Efficient and Thermally Stable All‐Polymer Solar Cells. Issue 45 (31st August 2020) - Fan, Qunping; Su, Wenyan; Chen, Shanshan; Liu, Tao; Zhuang, Wenliu; Ma, Ruijie; Wen, Xin; Yin, Zhihong; Luo, Zhenghui; Guo, Xia; Hou, Lintao; Moth‐Poulsen, Kasper; et al.
Abstract: A non‐conjugated polymer acceptor PF1‐TS4 was firstly synthesized by embedding a thioalkyl segment in the mainchain, which shows excellent photophysical properties on par with a fully conjugated polymer, with a low optical band gap of 1.58 eV and a high absorption coefficient >10 5 cm −1, a high LUMO level of −3.89 eV, and suitable crystallinity. Matched with the polymer donor PM6, the PF1‐TS4‐based all‐PSC achieved a power conversion efficiency (PCE) of 8.63 %, which is ≈45 % higher than that of a device based on the small molecule acceptor counterpart IDIC16. Moreover, the PF1‐TS4‐based all‐PSC has good thermal stability with ≈70 % of its initial PCE retained after being stored at 85 °C for 180 h, while the IDIC16‐based device only retained ≈50 % of its initial PCE when stored at 85 °C for only 18 h. Our work provides a new strategy to develop efficient polymer acceptor materials by linkage of conjugated units with non‐conjugated thioalkyl segments. Abstract : An efficient non‐conjugated polymer acceptor PF1‐TS4 was developed by embedding thioalkyl linkages in the mainchain of a conjugated polymer. The resulting all‐polymer solar cells achieved a promising device efficiency of 8.63 % with excellent thermal stability at 85 °C for 180 hours.